2019
DOI: 10.3389/fimmu.2019.00238
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Features of Human Amniotic Mesenchymal Stem Cells in Multiple Sclerosis: Immunomodulation, Inflammation Suppression, Angiogenesis Promotion, Oxidative Stress Inhibition, Neurogenesis Induction, MMPs Regulation, and Remyelination Stimulation

Abstract: Multiple sclerosis (MS) is an inflammatory and degenerative disorder of the central nervous system with unknown etiology. It is accompanied by demyelination of the nerves during immunological processes in the presence of oxidative stress, hypoxia, cerebral hypo-perfusion, and dysregulation in matrix metalloproteinases (MMPs). Human amniotic mesenchymal stem cells (hAMSCs) as pluripotent stem cells possess some conspicuous features which could be of therapeutic value in MS therapy. hAMSCs could mimic the cascad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 71 publications
(90 reference statements)
4
40
0
1
Order By: Relevance
“…Several studies have been conducted to test this approach in animal models of primary osteoporosis, aging, glucocorticoid-induced bone fragility, and fracture healing [8,10,11]. Our data, as well as those from others, have con rmed that MSCs have paracrine effects that reduce in ammation and restore angiogenesis and osteogenesis when they are localized within the bone microenvironment [11][12][13][14][15]. The current study aimed to for the study is to address the unmet medical needs for non-surgical therapy to reverse periodontal disease (PD)-induced bone loss, and test a new anabolic compound, LLP2A-Ale, in the treatment of PD-induced bone loss in a mouse model of PD.…”
Section: Introductionsupporting
confidence: 69%
“…Several studies have been conducted to test this approach in animal models of primary osteoporosis, aging, glucocorticoid-induced bone fragility, and fracture healing [8,10,11]. Our data, as well as those from others, have con rmed that MSCs have paracrine effects that reduce in ammation and restore angiogenesis and osteogenesis when they are localized within the bone microenvironment [11][12][13][14][15]. The current study aimed to for the study is to address the unmet medical needs for non-surgical therapy to reverse periodontal disease (PD)-induced bone loss, and test a new anabolic compound, LLP2A-Ale, in the treatment of PD-induced bone loss in a mouse model of PD.…”
Section: Introductionsupporting
confidence: 69%
“…oxidative stress inhibition (Abbasi-Kangevari et al 2019). Tsuji et al (2010) found that the hAD-MSCs xenografted to cure myocardial ischemia-reperfusion injury will differentiate into myocardial cells and restore partial myocardial function without rejection (Tsuji et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Stem cells (SCs) are self-renewing and undifferentiated cells capable of differentiating into more than 200 types of cells. The potential therapeutic effect of SCs is related to their role in cell differentiation, inflammation, immunomodulation and the stimulation of endogenous repair processes, such as angiogenesis and neurogenesis [7,8,9]. SC therapy has emerged as an encouraging regenerative tool in modern medicine, with potential applications in ischemic stroke as well as in other neurodegenerative disorders [10,11].…”
Section: Regenerative Tools In Modern Neurologymentioning
confidence: 99%